Research handbook on hate and hate crimes in society - Hawdon, James; Costello, Matthew (Edward Elgar Publishing, 2024)
"This comprehensive Research Handbook places the study of hate and hate crimes into historic and cross-national contexts, examining the reasons behind, and the effects of, the reported increase in hate crimes in recent years. James Hawdon and Matthew Costello bring together a diverse array of experts to highlight the ongoing empirical and conceptual challenges that scholars and practitioners face when studying this topic. Chapters address a variety of types of hate, including hate based on race, immigration status, religion, and sexual orientation, as well as the definitional and methodological issues involved in the study of hate. With findings from around the world, authors discuss both online and offline hate crimes in different cultural contexts. The Research Handbook assesses the complex relationship between hate crime and state actors, both in historic contexts and in contemporary society. Ultimately, it offers new insights into how to deal with the complexities of hate and understand its variability across both time and space. The Research Handbook on Hate and Hate Crime in Society is a vital read for students and scholars of criminology, sociology and discrimination. Due to its practical suggestions for intervention strategies and victim support, it will also appeal to practitioners working in the field of hate crime prevention"--